Brown Tumour of Jaw Bone: A Diagnostic Attribute of Hyperparathyroidism - Baral, Radha; Ojha, Bidhata; Bajracharya, Dipshikha; Bhattacharyya, Subrata; Roy, Saurabh; Singh, Sumit (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Brown tumour is an uncommon focal giant cell lesion that arises as a result of direct effect of parathyroid hormone on bone tissue in patients with hyperparathyroidism. The lesion is characterized by extensive bone resorption which is replaced by fibrovascular tissue and giant cell with abundant deposit of haemosiderin. A rare case of Brown tumour in maxilla and mandible in 57-year-old female patient is reported. This case report highlights the importance of detailed systemic investigation for all the maxillofacial lesions since it could be the diagnostic attribute of the systemic diseases.